"I do it my way": Idioms of practice and digital media ideologies of adolescents and older adults. (January 2022) - Fernández-Ardèvol, Mireia; Belotti, Francesca; Ieracitano, Francesca; Mulargia, Simone; Rosales, Andrea; Comunello, Francesca
This article analyzes the idioms of practice and media ideologies of adolescents and older adults regarding mobile digital media usage, and how they are negotiated within and between age cohorts. We formed aged-based focus groups in Rome and Barcelona (four groups of 16- to 19-year-olds and four of 65- to 85-year-olds). The comparison provides new insights on older individuals' communication practices, often overshadowed by the focus on youth. Participants of both age groups explained they do media in their own way, which is perceived as "the right" (or legitimate) way. Strategies and hierarchies differ with age, according to meanings and rankings attributed to media choices in a communicative environment of affordances, or polymedia. The results suggest that differentiated generation-based idioms of practice and media ideologies are in operation in each cohort while, in both cases, refer to adaptative and goal-oriented communications.